PENEGAKAN HUKUM OLEH POLRI TERHADAP TINDAK PIDANA PENGGELAPAN KENDARAAN BERMOTOR DALAM STATUS LEASING DIHUBUNGKAN DENGAN UNDANG-UNDANG NO. 42 TAHUN 1999 TENTANG JAMINAN FIDUSIA - HERI SURYADI (Program Studi Magister Ilmu Hukum Pascasarjana Universitas Langlangbuana, 2020)
Embezzlement motor vehicle credit from finance companies or leasing by the public is very harmful for the finance companies. In fact after the credit agreement is running, a lot of some people who commit a crime by not perform its obligations to pay installments of motor vehicles, and even then they sell, pledge, exchange, or lease a motor vehicle without the knowledge of the company. Such actions would very detrimental to the company and is also a crime of embezzlement that must be addressed jointly by the interested parties.